Statistical Optimization of Parameters for Eco-Friendly Dyeing of Cotton Using Direct Red 31 Dye. Issue 14 (28th October 2022) - Rehman, Fazal-ur-; Adeel, Shahid; Ahmad, Tanvir; Mateen, Abdul; Amin, Nimra
ABSTRACT: Effluent load produced by synthesis and application of synthetic dyes has led global community to empty sustainable tools during textile processing. Current study is the application of ultrasonic treatment for fabric pre-treated before desizing, before bleaching and before mercerization followed by dyeing using Direct Red 31 dye. It has been found that ultrasonic treatment to bleached fabric for 45 min has given high color strength using direct dye. FTIR analysis shows that US did not cause any chemical change but modify the surface of bleached fabric to make it more substantive for dye. Response surface methodology was employed for the optimization of dyeing conditions to make coloring process more sustainable under mild conditions. The statistical analysis reveals that under reduced optimal conditions shade made has not only show improvement in colorfastness rating but also enhanced the sustainability of fabric to uptake dye to much extend.